Ltb4r Gene Expression in Chronic Myeloid Leukemia in Iraq - Khaleel , Abdullah W.; Altaee, Maha Fakhry (Iraqi Journal of Science, 2023)
The current study was carried out to explore gene expression of the LTB4R gene with the development of chronic myeloid leukemia (CML) in Iraqi patients. The differences in the expression of this gene between patients and healthy controls were studied. The correlation of gender and age with CML patients compared with controls was included as well as the correlation of gene expression folding 2-ΔΔCt of LTB4R with clinical parameters (WBC, RBC, haemoglobin, platelets, and BCR-ABL gene). Results revealed significant increases in the mean of gene expression level (ΔCt) of patient groups compared to the corresponding ΔCt means in the healthy control group, the gene expression folding (2-∆∆Ct) of the LTB4R gene reflects significant differences in the expression showed the highest level in CML patients which reached to (9.12 ), no significant differences were exhibited according to age and gender between CML patients and control. The study revealed a non-significant positive correlation between LTB4R gene expression level with both the BCR-ABL gene and WBC. Our results concluded that the LTB4R gene expression level could act as a marker for the prognosis of CML.